Bina Kelompok Wanita Tani (KWT) “Kalpataru” Cetuskan Produk Unggulan Minuman Kesehatan Berupa Jamu - Ni Luh Gede Sujianingsih; Yanti Budiasih (Jurnal Kabar Masyarakat, 2024)
The initiative of the Women Farmers Group (WFG) "Kalpataru" in developing and promoting superior products based on health drinks in the form of herbal medicine. With a focus on the use of local and traditional ingredients, WFG "Kalpataru" seeks to introduce products that are not only beneficial for health, but can also improve the economy of group members. Jamu, which is an Indonesian cultural heritage, is processed with a recipe that has been modernized to meet the tastes and needs of today's consumers. This product combines traditional ingredients such as turmeric, temulawak, and ginger to create a health drink that is not only beneficial for health but also attractive to modern consumers. The herbal medicine produced is kencur rice, tamarind turmeric, butterfly pea kombucha and rosella kombucha. This study explores the product development process, from raw material research to marketing strategies. Through effective marketing strategies and education to consumers about the health benefits of the product, Bina WFG "Kalpataru" is committed to expanding market reach and improving the quality of life of the community through sustainable health product innovation.